Ethiopia's Second Novel - Fellman, Jack (Research in African literatures, 1994)
"Addis Alam" ("The New World") by Heruy Walda Sellasie was published in 1932 and was only the second original literary work in Amharic, the African-Semitic language that is the national language of Ethiopia. The novel and its author's life are examined.